Smart Shopping Tablet / Atiq Nadzirah Nasaruddin - Nasaruddin, Atiq Nadzirah (2020)
Nowadays, online shopping is growing 3 times faster than traditional retail. However, previous research found that most of the people still prefer in store shopping especially for those who wants to shop for groceries, food and clothing. It is because people would like to see and touch the product in person before they buy it. However, there are several problems encountered by the shoppers while doing in store shopping. Crowding and queuing in long line at billing counters is the main stressors when shopping products for regular used in supermarket. This is because customers have to wait in long queues to scan their products using barcode scanner and get it billed. This situation can leads to time consuming and it is inconvenient situation these day as people are living in a busy environment. Therefore, the company invents the new innovation product with RFID technology where able to total up the price of the items in the shopping trolley that can solve the problem faced by the shoppers during at the billing counter. The new innovation product also was invented with navigation or directory. It is specifically designed to assists the shoppers to find the product location within the store and avoid of wasting their time. The product location like aisle and shelf number will be displayed on the screen of the smart tablet. Moreover, the screen of the smart tablet able to display important information related to the store and items within the store. It is able to display the item with variety of brand and price. This information is important to avoid their purchasing items in not their budget limit. Additionally, the screen also can display about the specials offers and advertising the information of the store. It is to ensure that the shoppers will never miss out the great deals offered in the store. Since the tablet’s screen is the important part of the product, thus the company decided to cover it with high quality glass protector which is Gorilla Glass 5. It is to make sure that the screen of the smart tablet is not easily cracked and safe for long-term used.